Magnetic powder for coil components and coil components containing the same
Patent Information
- Application Number
- JP2023031124
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2016-11-01
- Filing Date
- 2023-03-01
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2037-06-05
AI Technical Summary
【0011】 本発明の一実施形態によるコイル部品用磁性粉末は、Fe-Si-B-C-Cr系の鉄系粉末を含み、上記鉄系粉末は非晶質粒子と結晶質粒子を含むため、高飽和磁束特性(Ms)を有することができる。
Smart Images

Figure 0007635284000001 
Figure 0007635284000002 
Figure 0007635284000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a magnetic powder for coil components and a coil component including the same. [Background technology]
[0002] An inductor is a type of coil component that is a typical passive element that, together with resistors and capacitors, configures an electronic circuit to remove noise. Inductors are used in combination with capacitors to configure resonant circuits and filter circuits that amplify signals in a specific frequency band using their electromagnetic properties.
[0003] Recently, the miniaturization and thinning of IT devices such as various communication devices and display devices is accelerating. Therefore, research is being continuously conducted to miniaturize and thin various elements such as inductors, capacitors, and transistors used in such IT devices.
[0004] Despite this miniaturization, there is a trend for the performance of coil components to remain the same as before or to be gradually improved. For inductors, which are one type of coil component, characteristics such as inductance (capacity), DC bias characteristics, and loss efficiency are considered important.
[0005] The performance of such coil components is greatly affected by the properties of the alloy powder used in the main body of the coil component.
[0006] Therefore, there is a need for magnetic powder for coil components that can improve the performance of the coil components. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Korean Patent Publication No. 2015-0038751 [Patent Document 2] Korean Patent Publication No. 2013-0094316 Summary of the Invention [Problem to be solved by the invention]
[0008] An object of the present invention is to provide a magnetic powder for coil components having high saturation magnetic flux characteristics (Ms) and a coil component including the same. [Means for solving the problem]
[0009] As a method for solving the above-mentioned problems, one example of the present invention proposes a magnetic powder for coil components, specifically, a Fe-Si-BC-Cr iron-based powder, the iron-based powder including amorphous particles and crystalline particles.
[0010] As a method for solving the above-mentioned problems, another embodiment of the present invention proposes a coil component, specifically, the coil component includes a main body containing magnetic powder for coil components, a coil disposed inside the main body with both ends exposed to the outside of the main body, and external electrodes disposed outside the main body and connected to the ends of the coil, respectively, the magnetic powder for coil components containing Fe-Si-BC-Cr iron-based powder, and the iron-based powder containing amorphous particles and crystalline particles. Effect of the Invention
[0011] The magnetic powder for coil components according to one embodiment of the present invention includes an Fe-Si-BC-Cr based iron-based powder, which includes amorphous particles and crystalline particles and thus can have high saturation magnetic flux characteristics (Ms).
[0012] In addition, a coil component according to another embodiment of the present invention includes an Fe-Si-BC-Cr-based iron-based powder, and the iron-based powder includes a magnetic powder for coil components that includes amorphous particles and crystalline particles, and therefore can have high DC-bias performance. [Brief description of the drawings]
[0013] [Figure 1] 1 is a graph showing the results of XRD (X-Ray Diffraction) measurement of the magnetic powder for coil components according to the comparative example, and an outline of the XRD signal of the magnetic powder consisting of only amorphous particles. [Diagram 2] The magnetic powder for coil components according to the comparative example was measured using a VSM (Vibrating Sample Magnetometer). [Diagram 3] 1 is a schematic diagram showing an XRD signal of a magnetic powder for coil components according to an embodiment of the present invention, which is measured by XRD (X-Ray Diffraction), and which is a mixture of amorphous particles and crystalline particles. [Figure 4] The magnetic powder for coil components according to one embodiment of the present invention was measured using a VSM (Vibrating Sample Magnetometer). [Diagram 5] 1 is a schematic diagram of XRD signals of magnetic powders with different crystalline particle contents. [Figure 6] 1 is a schematic diagram of XRD signals of magnetic powders with different crystalline particle contents. [Figure 7] 1 is a schematic diagram of XRD signals of magnetic powders with different crystalline particle contents. [Figure 8] The figures show the results of XRD measurement, TEM images and SAM patterns in the case where no crystalline peaks were observed. [Figure 9] The figures show the results of XRD measurements, TEM images and SAD patterns in cases where crystalline peaks were observed. [Figure 10] 13 is a schematic cross-sectional view of a coil component according to another embodiment of the present invention; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, preferred embodiments of the present invention will be described with reference to the accompanying drawings. However, the embodiments of the present invention can be modified into various other forms, and the scope of the present invention is not limited to the embodiments described below. Furthermore, the embodiments of the present invention are provided to more completely explain the present invention to those having average knowledge in the art. Therefore, the shapes and sizes of elements in the drawings may be enlarged or reduced (or highlighted or simplified) for clearer explanation, and elements indicated by the same reference numerals in the drawings are the same elements.
[0015] Magnetic powder for coil components A magnetic powder for coil components according to an embodiment of the present invention includes an Fe-Si-BC-Cr based iron-based powder, and the iron-based powder includes amorphous particles and crystalline particles.
[0016] The iron-based powder having high Ms characteristics used in conventional coil components means that the Fe content is 78 to 84 at%, the saturation magnetic flux density (Bs) is at the level of approximately 1.54 to 1.63 T, and the coercive force is at a level of 100 A / m or less.
[0017] In particular, in the case of magnetic powders that have been subjected to a specific heat treatment process, the coercive force is at a level of 100A / m or less, and the particle size distribution (D 50 ) is 20 to 25 μm, the magnetic permeability must be within the range of 32 to 35 at a frequency of 1 MHz based on a toroidal core, and the magnetic core loss must be 550 kW / m under the conditions of a magnetic flux density of 0.02 T (tesla) and a frequency of 1 MHz. 3 The following characteristics must be met:
[0018] In the case of iron-based powders with a high Fe content, in order to satisfy the above-mentioned properties, it is necessary to confirm that they contain amorphous particles when measured by X-ray diffraction (XRD).
[0019] The XRD signal of such an iron-based powder exhibiting amorphous properties and having a high Fe content exhibits a halo shape as shown in FIG.
[0020] FIG. 2 shows the Ms characteristics of the magnetic powder for coil components according to the comparative example containing only amorphous particles, as measured by VSM.
[0021] The magnetic powder for coil components according to the comparative example shown in FIG. 2 has a composition of 81 at% Fe, 4 at% Si, 13 at% B, 1 at% C, and 1% Cr, and is found to contain only amorphous particles, as shown in FIG. 1.
[0022] Referring to FIG. 2, it can be seen that the Ms of the magnetic powder for coil components according to the comparative example containing only amorphous particles is about 172.7 emu / g.
[0023] FIG. 3 is a schematic diagram showing an XRD signal of a magnetic powder for coil components according to an embodiment of the present invention, which is a mixture of amorphous particles and crystalline particles, measured by XRD (X-Ray Diffraction).
[0024] The magnetic powder for coil components according to an embodiment of the present invention used in the XRD and VSM measurements has a composition of 81 at% Fe, 4 at% Si, 13 at% B, 1 at% C, and 1% Cr, which is the same composition as the magnetic powder for coil components according to the comparative example described above.
[0025] Unlike the above-mentioned comparative examples, the magnetic powder for coil components according to one embodiment of the present invention is a heterogeneous powder in which amorphous particles and crystalline particles are mixed, and therefore, when measured by XRD, a peak (about 45 deg) corresponding to crystalline particles is confirmed.
[0026] That is, the magnetic powder for coil components according to one embodiment of the present invention contains an Fe-Si-BC-Cr based iron-based powder, and since the iron-based powder contains amorphous particles and crystalline particles, it can be confirmed from the measurement results of the XRD signal that the ratio h1 / h2 of the height h1 of the crystalline peak to the height h2 of the crystalline peak is 1 to 1.5.
[0027] In this case, the content of crystalline particles in the magnetic powder for coil components according to an embodiment of the present invention may be 5 to 6 vol %.
[0028] If the ratio h1 / h2 of the crystalline peak height h1 to the crystalline peak height h2 is less than 1, there is a problem that the core loss is very high and the Ms is low. If the ratio h1 / h2 of the crystalline peak height h1 to the crystalline peak height h2 exceeds 1.5, there is a problem that the magnetic permeability is low and the core loss is increased.
[0029] Therefore, when the ratio h1 / h2 of the crystalline peak height h1 to the crystalline peak height h2 is 1 to 1.5, it is possible to have low core loss characteristics, an appropriate level of magnetic permeability, and high Ms characteristics.
[0030] FIG. 4 shows the results of measuring the magnetic powder for coil components according to one embodiment of the present invention using a VSM (Vibrating Sample Magnetometer).
[0031] Referring to FIG. 4, since the magnetic powder for coil components according to one embodiment of the present invention is a heterogeneous powder in which amorphous particles and crystalline particles are mixed, despite having the same composition as the comparative example, the measurement results by VSM show that the Ms of the magnetic powder for coil components according to one embodiment of the present invention is about 182.6 emu / g, which is about 5 to 6% higher than the measured Ms value of the magnetic powder for coil components according to the comparative example.
[0032] To explain the measurement method in more detail, first, a magnetic powder for coil components according to a comparative example consisting only of amorphous particles having a composition of 81 at% Fe, 4 at% Si, 13 at% B, 1 at% C, and 1% Cr, and a magnetic powder for coil components according to one embodiment of the present invention having the same composition as the comparative example and a mixture of amorphous particles and crystalline particles were prepared.
[0033] Next, the prepared magnetic powder for coil components according to a comparative example and the magnetic powder for coil components according to an embodiment of the present invention were each adjusted to contain 70 to 90 wt % coarse powder and 10 to 30 wt % fine powder.
[0034] Thereafter, a toroidal core was manufactured using the magnetic powder for coil components according to the comparative example and the magnetic powder for coil components according to the embodiment of the present invention.
[0035] Next, the electromagnetic characteristics of the toroidal core according to the comparative example and the toroidal core according to the embodiment of the present invention were evaluated, and it was found that the levels of electromagnetic characteristics such as magnetic permeability, quality factor, and core loss were similar to each other.
[0036] However, the magnetic permeability (%) per input current was approximately 87.9% for the toroidal core according to the comparative example and approximately 90.8% for the toroidal core according to one embodiment of the present invention, confirming that the DC-bias performance of the toroidal core is high when amorphous particles and crystalline particles are mixed.
[0037] A magnetic powder for coil components according to one embodiment of the present invention may have an Fe content of 80 to 81 at%, a Si content of 4 to 8 at%, a B content of 12 to 14 at%, a C content of 0.15 to 1.0 at%, and a Cr content of 1 to 1.5 at%.
[0038] Coil components require a high Bs value, and the material design of alloy powders with high Bs is generally based on a composition rich in Fe elements.
[0039] Specifically, a master alloy (ingot) is made by adding small amounts of metalloid elements such as Si, B, and C to a composition rich in Fe, and then powdered using an atomizer. At this time, it is important to adjust the composition of the magnetic powder for coil components so that it can be vitrified (Glass Forming Ability (GFA)).
[0040] The magnetic powder for coil components according to one embodiment of the present invention has a high Bs value because the Fe content is 80 to 81 at %.
[0041] In addition, the magnetic powder for coil components according to one embodiment of the present invention has a Si content of 4 to 8 at%, a B content of 12 to 14 at%, and a C content of 0.15 to 1.0 at%, so that a portion of the magnetic particles can be vitrified.
[0042] In particular, the magnetic powder for coil components according to one embodiment of the present invention has a Cr content of 1.0 to 1.5 at %, and therefore has excellent corrosion resistance, prevents magnetic aging, and can achieve a Bs of 1.5 T or more.
[0043] In addition, the magnetic powder for coil components according to one embodiment of the present invention is obtained by adding 1 to 1.5 at % of Cr to the magnetic powder for coil components, and forming CrO on the surface of the Fe-Si-BC-Cr iron-based powder. x In this way, when the surface of the Fe-Si-BC-Cr iron-based powder is coated with a phosphate-based coating, the bonding between the Fe-Si-BC-Cr iron-based powder and the phosphate-based coating is significantly improved, and excellent insulation resistance characteristics and reproducibility can be ensured.
[0044] The aspect ratio of the iron-based powder contained in the coil component according to one embodiment of the present invention may be 1.1 to 1.3.
[0045] If the aspect ratio of the iron-based powder is less than 1.1, the core loss becomes large and the value of Ms becomes very low, whereas if the aspect ratio of the iron-based powder is more than 1.3, the powder has low permeability and high core loss characteristics.
[0046] In summary, the magnetic powder for coil components according to one embodiment of the present invention includes Fe-Si-BC-Cr iron-based powder, and the iron-based powder includes amorphous particles and crystalline particles. Therefore, based on a 20-mm toroidal core manufactured by mixing coarse powder and fine powder in a ratio of 8:2, the magnetic powder has a magnetic permeability of 32 or more at a frequency of 1 MHz and a core loss of 500 kW / m.3 Hereinafter, there is an excellent effect that the quality factor is 65 or more and a high Ms measurement value of 180 emu / g or more can be obtained.
[0047] 5 to 7 are schematic diagrams showing XRD signals of magnetic powders with different crystalline particle contents.
[0048] Specifically, FIG. 5 shows the XRD signal of the magnetic powder when h1 / h2 is 0, FIG. 6 shows the XRD signal when h1 / h2 is 1.3, and FIG. 7 shows the XRD signal when h1 / h2 is 2.82.
[0049] Meanwhile, the magnetic permeability (1 MHz), core loss, and Ms of the magnetic powders in Figs. 5 to 7 were measured.
[0050] As shown in Figure 5, when h1 / h2 is less than 1, i.e., when no crystalline peak is observed, the permeability is 21.6 and the core loss is 879 kW / m 3 , and Ms can be confirmed to be 172 emu / g.
[0051] In contrast, when h1 / h2 exceeds 1.5 as shown in Figure 7, the permeability is 17.3 and the core loss is 881kW / m 3 , and Ms can be confirmed to be 184.4 emu / g.
[0052] That is, when h1 / h2 is less than 1, there is a problem that the core loss is high and Ms is low, and when h1 / h2 exceeds 1.5, there is a problem that the core loss is high and the magnetic permeability is low.
[0053] However, as shown in Figure 6, when h1 / h2 is between 1 and 1.5, the magnetic permeability is 21.5 and the core loss is 717kW / m 3 , and Ms is 182 emu / g, indicating that the material has high permeability and Ms value as well as low core loss.
[0054] Figure 8 shows the results of XRD measurement, as well as the TEM image and SAM pattern when no crystalline peaks were observed, and Figure 9 shows the results of XRD measurement, as well as the TEM image and SAD pattern when crystalline peaks were observed.
[0055] 8 and 9, when a crystalline peak is observed in the XRD measurement results, it can be seen from the TEM photograph that amorphous particles and crystalline particles are mixed together, and in this case, it can be seen that the grain size (particle size) of the crystalline particles is about 9 to 10 nm.
[0056] Coil parts FIG. 10 is a schematic cross-sectional view of a coil device 100 according to another embodiment of the present invention.
[0057] Referring to FIG. 10, a coil device 100 according to another embodiment of the present invention includes a body 110, a coil 120 arranged inside the body 110 with both ends exposed to the outside of the body 110, and external electrodes 130 arranged outside the body 110 and respectively connected to the ends of the coil 120.
[0058] The main body 110 can be formed by stacking magnetic sheets 111, but is not limited to this.
[0059] The body 110 may be formed by including an alloy magnetic powder for a coil component according to an embodiment of the present invention.
[0060] A magnetic powder for coil components according to an embodiment of the present invention includes an Fe-Si-BC-Cr based iron-based powder, and the iron-based powder includes amorphous particles and crystalline particles.
[0061] That is, the magnetic powder for coil components according to one embodiment of the present invention contains an Fe-Si-BC-Cr based iron-based powder, and since the iron-based powder contains amorphous particles and crystalline particles, it can be confirmed from the measurement results of the XRD signal that the ratio h1 / h2 of the height h1 of the crystalline peak to the height h2 of the amorphous peak is 1 to 1.5.
[0062] Furthermore, the magnetic powder for coil components according to one embodiment of the present invention may have an Fe content of 80 to 81 at%, a Si content of 4 to 8 at%, a B content of 12 to 14 at%, a C content of 0.15 to 1.0 at%, and a Cr content of 1 to 1.5 at%.
[0063] The iron-based powder of the magnetic powder for coil components according to one embodiment of the present invention used when manufacturing coil components can contain 70 to 90 wt % of coarse powder and 10 to 30 wt % of fine powder.
[0064] When forming a coil component using the magnetic sheet 111, a coil pattern is formed in a spiral shape on the magnetic sheet 111, and the magnetic sheets 111 are stacked to connect adjacent coil patterns in the stacking direction via conductive vias to form the coil 120. When viewed in a projected plan view, the coil patterns of the coil 120 overlap each other to form a circular track.
[0065] The coil 120 is electrically connected to external electrodes 130 disposed on both end surfaces of the body 110 in the length direction L via leads.
[0066] In the coil component according to another embodiment of the present invention, the main body 110 contains the magnetic powder for a coil component according to one embodiment of the present invention, and therefore, can have the excellent effects as described above for the magnetic powder for a coil component according to one embodiment of the present invention.
[0067] Although the embodiments of the present invention have been described in detail above, it will be apparent to those skilled in the art that the technical scope of the present invention is not limited thereto, and that various modifications and variations are possible within the scope of the technical idea of the present invention described in the claims. [Item 1] Fe-Si-BC-Cr iron powder is included. The magnetic powder for coil components comprises magnetic particles, and each magnetic particle contains amorphous particles and crystalline particles. [Item 2] The result of measuring an XRD signal of the magnetic powder for coil components, 2. The magnetic powder for coil components according to item 1, wherein the ratio h1 / h2 of the height h1 of the crystalline peak to the height h2 of the amorphous peak is 1 to 1.5. [Item 3] 3. The magnetic powder for coil components according to item 1 or 2, wherein the content of the crystalline particles is 5 to 6 vol %. [Item 4] The Si content is 4 to 8 at%. The C content is 0.15 to 1.0 at%. 4. The magnetic powder for coil components according to any one of items 1 to 3, wherein the Cr content is 1 to 1.5 at %. [Item 5] 5. The magnetic powder for coil components according to any one of items 1 to 4, wherein the magnetic powder for coil components contains 70 to 90 wt % of coarse powder and 10 to 30 wt % of fine powder. [Item 6] 6. The magnetic powder for coil components according to any one of items 1 to 5, wherein the iron-based powder has an aspect ratio of 1.1 to 1.3. [Item 7] A body including magnetic powder for coil components; A coil is disposed inside the body, and both ends are exposed to the outside of the body; external electrodes disposed outside the body and connected to ends of the coil respectively; The magnetic powder for coil components is Fe-Si-BC-Cr iron powder is included. The iron-based powder includes magnetic particles, and each magnetic particle includes amorphous particles and crystalline particles. [Item 8] The result of measuring an XRD signal of the magnetic powder for coil components, 8. The coil component according to item 7, wherein a ratio h1 / h2 of a height h1 of a crystalline peak to a height h2 of an amorphous peak is 1 to 1.5. [Item 9] 9. The coil component according to item 7 or 8, wherein the content of the crystalline particles is 5 to 6 vol %. [Item 10] The Si content is 4 to 8 at%. The C content is 0.15 to 1.0 at%. 10. The coil component according to any one of items 7 to 9, wherein the Cr content is 1 to 1.5 at %. [Item 11] 11. The coil component according to any one of items 7 to 10, wherein the magnetic powder for coil components contains 70 to 90 wt % of coarse powder and 10 to 30 wt % of fine powder. [Item 12] 12. The coil component according to any one of items 7 to 11, wherein the iron-based powder has an aspect ratio of 1.1 to 1.3. [Explanation of symbols]
[0068] 100 Coil parts 110 Main unit 111 Magnetic Sheet 120 Coil 130 External electrode
Claims
1. An iron-based powder of the Fe-Si-B-C-Cr system having a B content of 12 to 14 at %, The iron-based powder includes magnetic particles, and each magnetic particle includes amorphous particles and crystalline particles, The crystalline particles include crystalline particles having a particle size of 9 to 10 nm. Magnetic powder for coil components.
2. 2. The magnetic powder for coil components according to claim 1, wherein the C content is 0.15 to 1.0 at %.
3. The Si content is 4 to 8 at %, The Cr content is 1 to 1.5 at%. The magnetic powder for coil components according to claim 1 or 2.
4. The result of measuring an XRD signal of the magnetic powder for coil components, The ratio h1 / h2 of the height h1 of the crystalline peak to the height h2 of the amorphous peak is 1 to 1.
5. The magnetic powder for coil components according to claim 1 .
5. The magnetic powder for coil components according to any one of claims 1 to 4, wherein the content of the crystalline particles is 5 to 6 vol %.
6. The magnetic powder for coil components according to any one of claims 1 to 5, wherein the magnetic powder for coil components contains 70 to 90 wt % coarse powder and 10 to 30 wt % fine powder.
7. The magnetic powder for coil components according to any one of claims 1 to 6, wherein the iron-based powder has an aspect ratio of 1.1 to 1.
3.
8. A body including magnetic powder for coil components; A coil is disposed inside the body, and both ends are exposed to the outside of the body; external electrodes disposed outside the body and connected to ends of the coil respectively; The magnetic powder for coil components is The iron-based powder includes an Fe-Si-B-C-Cr system having a B content of 12 to 14 at %, The iron-based powder includes magnetic particles, and each magnetic particle includes amorphous particles and crystalline particles, The crystalline particles include crystalline particles having a particle size of 9 to 10 nm. Coil parts.
9. The coil component according to claim 8, wherein the C content is 0.15 to 1.0 at %.
10. The Si content is 4 to 8 at %, The Cr content is 1 to 1.5 at%. The coil component according to claim 8 or 9.
11. The result of measuring an XRD signal of the magnetic powder for coil components, The ratio h1 / h2 of the height h1 of the crystalline peak to the height h2 of the amorphous peak is 1 to 1.
5. The coil component according to any one of claims 8 to 10.
12. The coil component according to any one of claims 8 to 11, wherein the content of the crystalline particles is 5 to 6 vol %.
13. The coil component according to any one of claims 8 to 12, wherein the magnetic powder for coil components contains 70 to 90 wt % of coarse powder and 10 to 30 wt % of fine powder.
14. The coil component according to any one of claims 8 to 13, wherein the iron-based powder has an aspect ratio of 1.1 to 1.3.
Citation Information
Patent Citations
Noise filter
JP1995041914A
Dust core and method for manufacturing same, and reactor using same
JP2007013072A
Fe-BASED AMORPHOUS ALLOY THIN STRIP
JP2009007639A
Dust core and method of manufacturing the same
JP2010114222A
Method for producing fe-group nano-crystal alloy, fe-group nano-crystal alloy, magnetic component, and device for producing fe-group nano-crystal alloy
JP2011256453A